Phylogeny and biogeography of Asthenopodinae with a revision of Asthenopus, reinstatement of Asthenopodes, and the description of the new genera Hubbardipes and Priasthenopus (Ephemeroptera, Polymitarcyidae) - Molineri, Carlos (2015)
The Neotropical species of Asthenopodinae are revised in a formal phylogenetic context. The five known species of Asthenopus Eaton, 1871, together with other five new species were included in a cladistic analysis using morphological characters (continuous and discretes). Representatives of the Afro-Oriental group of the subfamily (Povilla Navás, 1912 and Languidipes Hubbard, 1984) were also included to test the monophyletic hypothesis traditionally accepted for the group. Additional taxa representing the other subfamilies of Polymitarcyidae were incorparated: Ephoron Williamson, 1802 (Polymitarcyinae) and Campsurus Eaton, 1868, Tortopus Needham & Murphy, 1924 and Tortopsis Molineri, 2010 (Campsurinae). A matrix of 17 taxa and 72 characters was analyzed under parsimony resulting in a single tree supporting the monophyly of the subfamily Asthenopodinae. Other results include the monophyly of the Afro-Oriental taxa (Povilla and Languidipes), the paraphyletic nature of Neotropical Asthenopodinae, and the recognition of four South American genera: Asthenopus (including A. curtus (Hagen), 1861, A. angelae de Souza & Molineri, 2012, A. magnus sp. n., A. hubbardi sp. n., A. guarani sp. n.), Asthenopodes Ulmer, 1924, stat. n. (including A. picteti Hubbard, 1975, stat. n., A. traverae sp. n., A. chumuco sp. n.), Priasthenopus gen. n. (including P. gilliesi (Domínguez), 1988, comb. n.), and Hubbardipes gen. n. (including H. crenulatus (Molineri et al.), 2011, comb. n.). Descriptions, diagnoses, illustrations and keys are presented for all Neotropical taxa of Asthenopodinae (adults of both sexes, eggs and nymphs). Additionally a key to the subfamilies and genera of Polymitarcyidae is included. A quantitative biogeographic analysis of vicariance is presented and discussed through the study of the “taxon history” of the group.